A Randomized Single Blind Controlled Trial to Evaluate the Analgesic Effect by Application of Katuki Lepa and Lidocaine 2% Gel in Fissure in Ano - Aralikatti, Jagadeesh G; Emmi, S V; Kupati, Veena (International Research Journal of Ayurveda & Yoga, 2022)
Anal fissure is the common disease having the incidence of 30 to 40% of the population, young adult’s i.e.80-90% will have the posterior midline and rarely anterior. Parikartika is ‘Kartanavat vedana in Gudapradesh’ and it is not mentioned as a single disease ailment but explained as Vyapat, Purvarupa, Lakshana of other diseases. The aim and objective of this study was to evaluate to the analgesic effect by application of Katuki Lepa and lidocaine 2% gel in fissure in ano. Subjects were selected from attending Shalyatantra O.P.D of K.L.E’s Ayurveda Hospital Belgaum, Karnataka, India. Randomly fissure in ano subjects age between 20 to 60 yrs subjects are selected as per randomization chart. Each trial and control group containing 15 subjects were included in the study. In trail group Katuki Lepa applying externally daily once and continued for 7 days. In control group 2% lidocaine gel for external application daily once for 7 days. Subject was assessed daily for 7 days. Subjects showed improvement in aspects of decreasing pain and sphincter spasm. Pain reduction in treated group was 94.65 % in control group and 73.73% trial. Analgesics effect of effective in fissure in ano and helped in preventing fistula in ano as further complication.